SISTEM PENGELOLAAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN MANDIRI KOTA PAREPARE - Semaun, Syahriyah; Juneda, Juneda (DIKTUM: Jurnal Syariah dan Hukum, 2018)
: Law Number 40 of 2004 concerning the National Social Security System (SJSN) mandates that social security is mandatory for all residents including the National Health Insurance (JKN) through a Health Social Security Administering Agency (BPJS). This study discusses how the contract system in the Mandiri Health BPJS, how the mechanism for collecting contributions to the Mandiri Health BPJS, and how the quality of BPJS Health guarantees in Parepare City for health services for Mandiri Health BPJS participants. This study included a qualitative descriptive study with an analysis of Islamic economic law in the Office of BPJS Health in the City of Parepare. The results of the study indicate that the contract system in the Independent Health BPJS in the City of Parepare is in accordance with Islamic economic law and the mechanism for collecting contributions from Mandiri Health BPJS participants is not in accordance with Islamic economic principles. Quality assurance of BPJS Kesehatan in the City of Parepare for health services for participants of the Independent Health BPJS in accordance with Islamic economic law.